Russia in Asia
1 online resource (xv, 240 pages)
Keywords: "This edited volume presents new research on Russian-Asian connections by historians, art historians, literary scholars, and linguists. Of particular interest are imagined communities, social networks, and the legacy of colonialism in this important arena of global exchanges within the imperial, Soviet, and post-Soviet eras. Individual chapters investigate how Russians imagined Asia and its inhabitants, how these different populations interacted across political and cultural divides, and how people in Siberia, China, and other parts of Asia reacted to Russian imperialism, both in its formal and informal manifestations. A key strength of this volume is its interdisciplinary approach to the topic, challenging readers to synthesize multiple analytical lenses to better understand the multivalent connections binding Russia and Asia together"--